PENGARUH NPL, CAR, LDR, LTA, GWM DAN GDP TERHADAP KINERJA KEUANGAN BANK UMUM PERSERO DI INDONESIA PERIODE 2008-2015 - ANDRIYANI, NOVI (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this research is to understand the influence of non performing loan, capital adequacy ratio, loan to deposit ratio, liquid asset to total asset, legal reserve requirement, and gross domestic product on financial performace in bank. In this research, reseacher use roa to measure financial performance. The object of this study were bank persero listed at bank indonesia period 2008-2015. The study uses a quantitative approach, and used are secondary data. The methods of data analysis were multiple regresion models. The result of this study indicated that non performing loan variable has a negative and significant on financial performance. Capital adequacy ratio variable has no influence on financial performance because to the element of prudential bank in diverting funds from the equity placement. Loan to deposit ratio variable has a negative and significant. Liquid asset to total asset variable has no influence on financial performance because the size of the cash that must be owned byn the bank depends on the characteristic of the bank. Legal reserve requirement variable has no influence on financial performance because the minimum legal reserve requirement not get invcome. Gross domestic product on financial variable has no influence on financial performance because it does not affect the demand for bank credit that will have an impact on income. Keywords : financial performance, banking, macro economy, internal bank.